Efficacy of yeast beta-glucan 1,3/1,6 supplementation on respiratory infection, fatigue, immune markers and gut health among moderate stress adults in Klang Valley of Malaysia: protocol for a randomised, double-blinded, placebo-controlled, parallel-group study - Suzana Shahar; Kalavathy Ramasamy; Norhayati Ibrahim; Nur Nadia Mohamad Habibullah; Munirah Ismail; Mohd Zul Amin Kamaruddin; Shirley Gee Hoon Tang; Mohd Faisal Abdul Hamid (BMJ Open)
Introduction Yeast beta-glucan (YBG) are recognised for enhancing the immune system by activating macrophages, a key defence mechanism. Given the global prevalence and impact of upper respiratory tract infections (URTIs) on productivity and healthcare costs, YBG has shown promise as a potential therapeutic and preventive strategy for recurrent respiratory tract infections. However, little is known regarding the efficacy of YBG at lower dosages in relation to URTI, fatigue, immune response and uncertainties of how they affect the gut microbiota composition.Methods and analysis This 12-week randomised, double-blinded, placebo control, parallel-group clinical trial aims to evaluate the efficacy of YBG 1,3/1,6 on respiratory tract infection, fatigue, immune markers and gut health among adults with moderate stress. The study involves 198 adults aged 18–59 years with moderate stress levels as assessed using Perceived Stress Scale 10 (score 14–26) and Patient Health Questionnaire 9 (score ≥9); and had symptoms of common colds for the past 6 months as assessed using Jackson Cold Scale. These participants will be randomised into three groups, receiving YBG 1,3/1,6 at either 120 mg, 204 mg or a placebo. The outcomes measures include respiratory infection symptoms, fatigue, mood state and quality of life assessed using Wisconsin Upper Respiratory Symptoms Scale, Multidimensional Fatigue Inventory, Profile of Mood State and Short Form 36 Health Survey Questionnaire, respectively. In addition, full blood analysis and assessment of immune, inflammatory and oxidative stress biomarkers will be taken. Secondary outcome includes gut microbiota analysis using stool samples via 16S rRNA sequencing.Ethics and dissemination The research protocol of the study was reviewed and approved by the Research Ethics Committee of Universiti Kebangsaan Malaysia (UKM/PPI/111/8/JEP-2023–211). The findings will be disseminated to participants, healthcare professionals and researchers via conference presentations and peer-reviewed publications.Trial registration number ISRCTN48336189